2013
DOI: 10.1038/nsmb.2646
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional processing of pri-miRNAs with branched terminal loops by Arabidopsis Dicer-like1

Abstract: miRNAs originate from primary transcripts (pri-miRNAs) with characteristic stem-loop structures. Accurate processing of pri-miRNAs is required for functional miRNAs. Here, using pri-miR166 family as a paradigm, we report the decisive role of pri-miRNA terminal loops in miRNA biogenesis. We found that multi-branched terminal loops in pri-miR166s substantially suppressed miR166 expression in vivo. Unlike canonical processing of pri-miRNAs, terminal-loop-branched (TLBed) pri-miRNAs can be processed by Dicer-like1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
136
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(157 citation statements)
references
References 44 publications
5
136
1
5
Order By: Relevance
“…Loop-to-base processing occurs in specific cases, such as miR159 and miR319 (Bologna et al, 2009). A unique case of bidirectional processing was observed for miR166, where it seems to play a regulatory role (Zhu et al, 2013). Plants also have non-canonical miRNAs, such as mirtrons, which skip the first cleavage step by DCL1 (Meng and Shao, 2012).…”
Section: Rdr6mentioning
confidence: 99%
“…Loop-to-base processing occurs in specific cases, such as miR159 and miR319 (Bologna et al, 2009). A unique case of bidirectional processing was observed for miR166, where it seems to play a regulatory role (Zhu et al, 2013). Plants also have non-canonical miRNAs, such as mirtrons, which skip the first cleavage step by DCL1 (Meng and Shao, 2012).…”
Section: Rdr6mentioning
confidence: 99%
“…In Arabidopsis thaliana, four DCLs display specialized functions by producing specific sRNA products (Bologna and Voinnet 2014). The precise processing of microRNAs (miRNAs) from imperfect, foldback endogenous transcripts is mostly dependent on DCL1, the activity of which is aided by the RNA-binding partner Hyponastic Leaves 1 (HYL1) and Serrate (Kurihara et al 2006;Dong et al 2008;Zhu et al 2013). The other three DCLs participate in the production of small interfering RNAs (siRNAs).…”
Section: Introductionmentioning
confidence: 99%
“…Plant miRNA precursor can be processed either base-to-loop or loop-to-base or bidirectional, depending on the secondary structures. In longer stems, the processing is sequential producing one or more miRNA/miRNA* duplex (Zhu et al, 2013;Cuperus et al, 2009;Bologna et al, 2009;Mateos et al, 2010;Werner et al, 2010;Song et al, 2010). Three independent research groups (Song et al, 2010;Werner et al, 2010;Mateos et al, 2010) using mutagenesis based structure-function approach on selected conserved miRNAs have shown that in base-to-loop processing, the first cut mediated by DCL1 and its partners is made ~15-nt upstream of a big bulge or ssRNA-dsRNA junction from the base.…”
Section: Structural Determinants Of Mirna Biogenesismentioning
confidence: 99%